An examination of the potential benefits of expert guided physical activity for supporting recovery from extreme social withdrawal: Two case reports focused on the treatment of Hikikomori - Yokoyama, Keiko; Furuhashi, Tadaaki; Yamamoto, Yuji; Rooksby, Maki; McLeod, Hamish J. (Frontiers in Psychiatry, 2023)
Extreme and long-term social withdrawal, first described in Japan as Hikikomori, has now become a globally recognized mental health problem. Intervention studies severely lag behind epidemiological and phenomenological research. We present two descriptive case reports of Japanese university students with Hikikomori who participated in an early phase test of a structured intervention involving physical activities that was developed and facilitated by clinicians and physical education specialists—Human Movement Consultation (HMC). The two male recipients (19 and 29-years old at the start of treatment) completed approximately 40 consultation sessions delivered over three years consisting of a combination of outdoor workouts (i.e. walking, running, and cycling) and interpersonal sports (e.g. table tennis, badminton, and tennis). Changes in social withdrawal behavior were independently rated from clinical health records using a structured scale (the Glasgow Hikikomori Scale; GHS). Behavioral observations and scale data for both cases indicated improvements from pre-treatment levels of social withdrawal. At the end of the intervention, both had returned to normative levels of functioning. Case A returned to university and Case B secured a new job and returned to the workforce. To help advance our understanding of treatment options, these case descriptions analyse potential change mechanisms in order to understand how HMC can support recovery from extreme social withdrawal. One key observation is that both outdoor workouts and interpersonal sports offer a non-threatening method of enabling Hikikomori to engage in interpersonal interactions. Such connections via structured activities may allow the reinstatement of social skills in a graded manner. In addition, an initial focus on physical experiences may help promote psychological and social connectedness without triggering the social fears and challenges that underlie the Hikikomori state. The findings from these two cases offer a framework to guide further research and the development of exercise-based interventions for this hidden and often neglected group.